Contrast of hydraulic conductivity induces transport of combined pollutants in high- and low-permeability systems - Zhongran Wu; Shengyu Wu; Yao Hou; Min Zhang; Jianhong Liang; Chao Cai (Ecotoxicology and Environmental Safety)
The transport process of pollutants in the environment can be influenced by heterogeneous geologic architecture and pollutant interactions. However, there has been a lack of research on co-transport behaviors of combined pollutants in heterogeneous aquifers. In this study, a series of two-dimensional tank experiments were carried out to study the transport behavior of toluene and naphthalene in both homogeneous and heterogeneous aquifers. The results revealed that the coexisting solutes facilitated the transport of toluene and naphthalene in the homogeneous aquifers, potentially due to competitive adsorption between these compounds. In the high- and low-permeability systems, the transport rates for both toluene and naphthalene decreased while exhibiting characteristics such as early arrival, long tails, and multiple peaks. The spatial analysis of pollutant distribution indicated that hydraulic conductivity contrast played a critical role in inducing back diffusion phenomenon. Furthermore, toluene exhibited more pronounced matrix diffusion compared to naphthalene in heterogeneous aquifers, characterized by higher concentrations, wider diffusion range in low-permeability zones. And the β value for toluene is smaller than naphthalene in CTRW model, indicating that the former is more sensitive to the hydraulic conductivity contrast. This study provides novel insights into understanding the co-transport behavior of combined pollutants in heterogenous aquifers.